Efektivitas Acceptance and Commitment Therapy (ACT) dalam Memoderasi Quarter-Life Crisis pada Lulusan Baru salah satu Perguruan Tinggi Swasta di Bandung - Ignatia Ria Natalia; Missiliana Riasnugrahani; Robert Oloan Rajagukguk (Humanitas (Jurnal Psikologi), 2023)
Fresh graduates in their early adult development are vulnerable to experiencing a quarter-life crisis. This study uses Acceptance and Commitment Therapy in dealing with the quarter-life crisis. Three fresh graduates participated in this research. They were given the Quarter-Life Crisis measurement tool and The Comprehensive Assessment of Acceptance and Commitment Treatment Process tool before being given the Acceptance and Commitment Therapy intervention in 4 sessions for two weeks. The results of this study show, Acceptance and Commitment Therapy can reduce scores of indecisiveness in making decisions, desperation, negative self-judgment, being stuck in a tough situation, anxiety, depression, and worried about interpersonal relationships that are being and will be built for the fresh graduates. It also can increase the scores of defusion, self as a context, acceptance, values, flexibles at the present moment, and committed action for fresh graduates. Both of the results show that the intervention is having an impact on fresh graduates. Even so, the research is not significant from a quantitative analysis standpoint.